Perkosaan dalam Relasi Pacaran: Manifestasi Relasi Kuasa dan Kontrol atas Tubuh Perempuan - Yuwita Margareth; Elizabeth Kristi Poerwandari (Jurnal Kajian Gender dan Anak, 2025)
Rape is achieved through manipulation and intimidation. Rape can occur in a dating relationship and be committed by a boyfriend. Rape is understood with a false belief that harms women. Rape is carried out as a form of power relations to subjugate and degrade women. This research aims to explain that rape is an oppression of women through the domination and control of women’s bodies. The research method was through a literature review of 20 research journal articles on rape. The results show that patriarchy continues to be present in its from through rape as an oppression that signifies the existence of power and control over women.